Предмет: Алгебра,
автор: Prohoji
Решите уравнение (892)
Приложения:
Ответы
Автор ответа:
0
1/(x-3)-14/(x³-x²-9x-9)=1/(x²+2x-3)
1/(x-3)-14/(((x²(x-1)-9(x-1))=1/((x-1)(x+3))
1/(x-3)-14/((x²-9)(x-1))=1/((x-1)(x+3)
1/(x-3)-14/((x-3)(x+3)(x-1))=1/((x-1)(x+3))
ОДЗ: x-3≠0 x≠3 x+3≠0 x≠-3 x-1≠= x≠1
(x+3)(x-1)-14=x-3
x²+2x-3-14-x+3=0
x²+x-14=0
x₁=(-1+√57)/2 x₂=(-1-√57)/2.
1/(x-3)-14/(((x²(x-1)-9(x-1))=1/((x-1)(x+3))
1/(x-3)-14/((x²-9)(x-1))=1/((x-1)(x+3)
1/(x-3)-14/((x-3)(x+3)(x-1))=1/((x-1)(x+3))
ОДЗ: x-3≠0 x≠3 x+3≠0 x≠-3 x-1≠= x≠1
(x+3)(x-1)-14=x-3
x²+2x-3-14-x+3=0
x²+x-14=0
x₁=(-1+√57)/2 x₂=(-1-√57)/2.
Похожие вопросы
Предмет: Геометрия,
автор: ivankor56
Предмет: Математика,
автор: hiker78
Предмет: Физика,
автор: maksukovaolga55
Предмет: Алгебра,
автор: tghfye58971
Предмет: Математика,
автор: Andnech